Central African Republic : Statistical Annex. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
In this study, the following statistical data are presented: GDP at current prices, agricultural production, cotton production and producer prices, production and exports of forestry products, electricity price structure, consumption of oil products, consumer price index, wholesale price index, central government operations and revenue, interest rate structure, monetary survey, supply and use of resources at current prices, producer prices of major agricultural commodities, costs and prices in the cotton sector, livestock population and slaughtering, industrial production index, composition of exports, and so on.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet